Macro-anatomical investigations on the skeletons of porcupine (Hystrix cristata). Part III: Skeleton axiale - Yilmaz, S (Blackwell Wissenschafts-Verlag Gmbh, 1998)
The aim of this study was to investigate the axial skeleton of two porcupines (Hystrix cristata). The important features of the skull, observed in this study are as follows: The zygomatic process of frontal bone (os frontale) was found to be rudimentary, and the infraorbital foramen (for. infraorbitale) was very large. The zygomatic bone (os zygomaticum) has two processes (frontal and temporal) and the zygomatic arch (arcus zygomaticum) was composed of three bones. The dental formulae were 2 (I 1/1, C 0/0, P 1/1, M 3/3) = 20. The angular process (Proc. angularis) of mandible is well developed. The vertebral formula was found as C-7, T-15, L-4, S-4, Ca-12. All of cervical vertebrae had the transverse foramen (for. transversarium). The first eleven spinous processes (proc. spinosus) of thoracic vertebrae were caudally-sloped, the twelfth as the anticlin vertebrae and the last three were directed cranially. Hemal arches (or ossa arcus hemalis) were presented as separate bones which articulate with the ventral surfaces of the caudal ends of the bodies of the second, third and fourth caudal vertebrae.